LASSA FEVER MEDIA CAMPAIGNS: EXAMINING THE INFLUENCE ON THE HEALTH BEHAVIOUR OF ENUGU RESIDENTS - Ukaegbu, Michael Ibe, Ph.D., Ukaegbu, Michael Ibe, Ph.D.; Efetobor, O. Elijah (BW Academic Journal, 2022)
During health emergencies like Lassa fever outbreak, there is general hunger for information, as a way of staying healthy. This no doubt, account for the sharp increase of audiences’ (listeners and viewers) during such periods. Hence the need to investigate the influence of Lassa fever media campaigns on the health behaviour of Enugu State residents forms the fulcrum of this research. The study, has as specific objective of determining the level of awareness of Lassa fever risk factors, prevention, treatment, and practice among residents of Enugu State. The Explanatory Mixed Method Design was adopted for this study. From a projected population estimate of 4,411,100, a sample size of 384 was drawn using the automated online sample size calculator advanced by Wimmer and Dominick (2013) with confidence level of 95% and confidence interval of 5.0%. Instruments for data collection was questionnaire and in-depth interview while SPSS was used in analyzing the generated data. The qualitative data generated through interview were used to complement the quantitative data generated using the questionnaire. The qualitative data from interview were discursively presented in prose-like manner in tables. It was discovered that the broadcast media influenced the health behaviour of people positively as it concerns Lassa fever risks factor, testing, prevention and practice. Premised on data evidence, the researchers drew a reasoned conclusion that by giving health emergencies like the Lassa fever outbreak the needed attention, media can help reduce or totally eliminate mortality ratios in times of diseases and viruses outbreaks through their various awareness and sensitization campaigns. The need for health advocacy was suggested. That is, the use of opinion leaders, particularly religious and traditional leaders to spread the gospel of healthy living be adopted.